Chronic jet lag-like conditions dysregulate molecular profiles of neurological disorders in nucleus accumbens and prefrontal cortex - Siddique, Rabeea; Awan, Faryal Mehwish; Nabi, Ghulam; Khan, Suliman; Xue, Mengzhou (Frontiers in Neuroinformatics, 2022)
Background: Patients with neurological disorders often display altered circadian rhythm. The disrupted circadian rhythms through chronic jetlag or shiftwork are thought to increase the risk and severity of human disease including cancer, psychiatric diseases and other brain diseases. Results: In this study, we investigated the impact of shiftwork or chronic jetlag (CJL) like conditions on mice’s brain. Transcriptome profiling based on RNA sequencing revealed that genes associated with serious neurological disorders were differentially expressed in the nucleus accumbens (NAc) and prefrontal cortex (PFC). Similarly, qPCR analysis showed that a number of key regulatory genes linked with neurological disorders were significantly altered in NAc, PFC, hypothalamus, hippocampus, and striatum. Serotonin levels, as well the expression levels of serotonin transporters and receptors were significantly altered in mice treated with CJL. Conclusions: Overall, these results indicate that CJL may increase the risk of neurological disorders by disrupting the key regulatory genes, biological functions, serotonin, and corticosterone. These molecular linkages can further be studied to investigate the mechanism underlying CJL or shiftwork mediated neurological disorders in order to develop treatment strategies.